2020
DOI: 10.1080/14756366.2020.1748024
|View full text |Cite
|
Sign up to set email alerts
|

Imidazopyridine-fused [1,3]diazepinones: modulations of positions 2 to 4 and their impacts on the anti-melanoma activity

Abstract: A series of 19 novel pyrido-imidazodiazepinones, with modulations of positions 2, 3 and 4 of the diazepine ring were synthesised and screened for their in vitro cytotoxic activities against two melanoma cell lines (A375 and MDA-MB-435) and for their potential toxicity against NIH-3T3 non-cancerous cells. Selected compounds were also evaluated on the NCI-60 cell line panel. The SAR study revealed that the molecular volume and the cLogP of compounds modified at position 2 were significantly correlated with the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

5
0

Authors

Journals

citations
Cited by 8 publications
(20 citation statements)
references
References 26 publications
(57 reference statements)
0
20
0
Order By: Relevance
“…Briefly, while positions 3 and 5 could be modified without losing activity, various aromatic nuclei could be introduced in position 2 of the ring. In this case a correlation was found between the cytotoxic activity of the compound, its logP and the molecular volume of the introduced substituent 288 . Regarding position 4, the S stereochemistry was crucial for the activity and short linear alkyl chains were tolerated.…”
Section: Activity On Unknown Targetsmentioning
confidence: 83%
See 3 more Smart Citations
“…Briefly, while positions 3 and 5 could be modified without losing activity, various aromatic nuclei could be introduced in position 2 of the ring. In this case a correlation was found between the cytotoxic activity of the compound, its logP and the molecular volume of the introduced substituent 288 . Regarding position 4, the S stereochemistry was crucial for the activity and short linear alkyl chains were tolerated.…”
Section: Activity On Unknown Targetsmentioning
confidence: 83%
“…The most active compounds were also tested on the healthy fibroblast NIH3T3 cell line. They did not show any significant toxicity on this cell line, even at high concentration (100 µM), suggesting a good selectivity of these compounds for cancer cells 287,288 . Additional studies showed that JMV5038 and some of these analogues induced an increase in the proportion of cells in the G2/M phase, and an appearance of cells in the subG1 phase 288 .…”
Section: Activity On Unknown Targetsmentioning
confidence: 90%
See 2 more Smart Citations
“…Although much progress has been made to increase patient responses (use of immunotherapies and/or drugs combination), development of new compounds or strategies to limit the occurrence of resistance in melanoma cell lines is still in demand. [ 137–139 ]…”
Section: Serine‐threonine Kinases (Stks) Degradersmentioning
confidence: 99%